Comparison of the Effectiveness of Infinite Tomatis Sound Therapy, Vestibulo-Cerebellar Skills Training, and the Combination of Both Methods on Response Inhibition in Students with Specific Learning Disorder with Reading Impairment - Abedi, Somayeh; Ashayeri, Hasan; Esteki, Mahnaz; Salehi, Mahdieh (Psychological Research in Individuals with Exceptional Needs, 2025)
The present study aimed to compare the effectiveness of Infinite Tomatis sound therapy, vestibulo-cerebellar skills training, and the combination of both methods on response inhibition in students aged 8 to 12 years with specific learning disorder characterized by reading impairment. This research was an applied study utilizing a quasi-experimental design with pre-test, post-test, and follow-up stages accompanied by a control group. The statistical population consisted of all students with reading difficulties in Tehran in 2024 who sought treatment at counseling and rehabilitation clinics. The sample included 60 students from this population who were selected through convenience sampling and randomly assigned to four groups: Infinite Tomatis sound therapy training (n=15), vestibulo-cerebellar skills training (n=15), combined Infinite Tomatis sound therapy and vestibulo-cerebellar skills training (n=15), and a control group (n=15). After the intervention sessions, participants in all three experimental groups completed the research questionnaires again. The data were collected using the Reading and Dyslexia Test (NAMA) by Karami Nouri et al. (2008), the IVA2 Test, and the Go/No-Go Test developed by Bruner and Hoffman (1984). Data analysis was performed using repeated measures ANOVA with SPSS version 22. The findings indicated a significant difference in response inhibition scores between the combined training group and the vestibulo-cerebellar skills training group. Specifically, the response inhibition scores in the combined training group were higher than those in the vestibulo-cerebellar skills training group.